ANALISIS YURIDIS WANPRESTASI TERHADAP AKTA PENGAKUAN HUTANG DALAM PERJANJIAN KERJASAMA PEMASUKAN MODAL (Studi Putusan Mahkamah Agung Nomor 191 K/Pdt/2019) - Jonatan Samosir; Mustamam Mustamam; Adil Akhyar (LPPM YPITI, 2021)
Default in the implementation of capital investment cooperation agreements is a phenomenon that often occurs in practice. Many factors cause default, it could be due to the fault of the parties or outside the fault of the parties. The formulation of the problem in this thesis is how the legal strength of the debt recognition deed in the capital investment cooperation agreement, what is the legal effect of default on the debt recognition deed in the capital investment cooperation agreement, how is the legal consideration of the judge judge in deciding case No. 191 K / Pdt / 2019. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results show that the legality of the debt recognition deed in the capital investment cooperation agreement is a perfect means of evidence for the parties in the event of a dispute in court. As a result of the default law on the deed of debt recognition in the capital investment cooperation agreement, the injured party sues so that the party causing the loss is required to provide compensation as stipulated in the cooperation agreement which determines that the party who breaks the promise is willing to be sued and bear all costs arising from the collection the. Judge Judge's legal considerations in deciding case No. 191 K / Pdt / 2019 is that the agreement has been valid and binds the parties as law, so that the legal relationship between the plaintiff and the defendant is a debt and credit relationship accompanied by interest in which the plaintiff and defendant agree that the plaintiff is the creditor (creditor) while the defendant is an indebted party (debtor) provided that the defendant must repay the loan within 3 (three) months, accompanied by profit payments.